Sara Hildénin Taidemuseo / Sara Hildén Art Museum : International modern paintings, sculptures and drawings. (Tampere : Sara Hildénin taidemuseo, 2000)
Albers, Josef ; Alviani, Getulio ; Antes, Horst ; Arman ; Bacon, Francis ; Bellmer, Hans ; Bernik, Janez ; Bettencourt, Pierre ; Bill, Max ; Bissier, Julius ; Bissière, Roger ; Blais, Jean-Charles ; Bonnard, Pierre ; Botero, Fernando ; Brauner, Victor ; Breivik, Bard ; Buraglio, Pierre ; Campbell, Steven ; Pizzi Cannella, Piero ; Canogar, Rafael ; Cassel, Axel ; De Chirico, Giorgio ; Christo ; Copnall, John ; Cragg, Tony (Anthony) ; Cucchi, Enzo ; Delvaux, Paul ; Dubuffet, Jean ; Duchene, Gerard ; Eegyvudluk ; Farreras, Francisco ; Fautrier, Jean ; Fontana, Lucio ; Gallo, Frank ; Giacometti, Alberto ; Gris, Juan ; Guitet, James ; Hartung, Hans ; Hucleux, Jean-Olivier ; Hultén, Carl-Otto ; Ipousteguy, Jean ; Johnson, Dennis ; Kanovitz, Howard ; Katz, Alex ; Kienholz, Edward ; Klee, Paul ; Kolar, Jiri ; Kramer, Harry ; Kubach-Wilmsen-Team ; Laurencin, Marie ; Leger, Fernand ; Parc, Julio Le ; Lin, Richard ; Long, Richard ; López, Francisco ; Lorenzo, Antonio ; Magnelli, Alberto ; Maillol, Aristide ; Manessier, Alfred ; Marchelli, Mirco ; Miki, Tomio ; Minguzzi, Luciano ; Miro, Joan ; Molin, Lei ; Moore, Henry ; Morandi, Giorgio ; Mortensen, Richard ; Motherwell, Robert ; Neumann, Max ; Nieto, Rodolfo ; Peinado, Francisco ; Perez, Augusto ; Picasso, Pablo ; Pinchon, Jean Claude ; Poliakoff, Serge ; Procktor, Patrick ; Quintanilla, Isabel ; Quintero, Daniel ; Raysse, Martial ; Richier, Germaine ; Rouault, Georges ; Santomaso, Giuseppe ; Sato, Key ; Schoonhoven, Jan ; Schwitters, Kurt ; Schoffer, Nicolas ; Scott, William ; Segal, George ; Segui, Antonio ; Sobrino, Francisco ; Solano, Susana ; Sota, Jesus de la ; Soto, Jesus Rafael ; Soulages, Pierre ; de Staël, Nicolas ; Sugai, Kumi ; Sutherland, Graham ; Takamatsu, Jiro ; Tanguy, Yves ; Tàpies, Antoni ; etc.
Engels & Fins
Sara Hildén Art Museum : Own collections : summer exhibition, Sara Hildén Art Museum / Sara Hildénin Taidemuseo, Tampere, 06.06. - 27.08.2000
kunstcatalogus